Sacakhaṇḍa darashana : Japujī sāhiba wica waranaṇa kīte pañjāṃ khaṇḍāṃ, dharama khaṇḍa, giāna khaṇḍa, sarama khaṇḍa, karama khaṇḍa, sacakhaṇḍa te hora sambandhata prakaraṇāṃ dī niraṇe pūrbaka wiākhayā - Raṇadhīra Siṅgha, b. 1879 (SAMP early 20th-century Indian books project ;, 1942)
Interpretative study of Sikh religious philosophy as represented in Japujī, by Guru Nanak, 1469-1538.